Investment and environmental management: The interaction between environmentally responsible investment and environmental management practices - Weber, Olaf (International Journal of Sustainable DevelopmentInternational Journal of Sustainable Development, 2006)
Do investors, such as environmentally responsible funds, influence firms' decisions to implement environmental management practices? We present the results of a survey analysing the implementation standards of environmental management practices subject to the influence of environmentally responsible investment funds. Results indicate that firms listed in environmentally responsible funds perform better in their environmental management practices. However, this good performance does not seem to be influenced by the desire of a firm to be listed in an environmentally responsible fund but by other reasons, i.e. a certified environmental management system.